Human Trafficking : the Gap between International regulation and Enforcement - Leech, Tasha Nicole; Trávníčková, Zuzana, 1977-; Burešová, Jana, 1989-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
The goal of this thesis is to provide insight as to why the number of trafficking cases and convictions is still relatively low compared to the total volume of trafficking occurring, even though the trade is increasingly addressed by international law. Through a study of trafficking itself, a summary of current international legislation, and an analysis of the implementation of said legislation this thesis will show that the gap between legislation and enforcement can be partially accounted for by a widespread failure by states to adequately address the demand for trafficked persons in their national legislation. While this is far from a complete explanation of the problem it is an important piece of the puzzle.
Vedoucí práce: Zuzana Trávníčková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses